Improving multicultural learning through interpretations and interactions with museum educational practice. Issue 1 (2nd January 2016) - Dimas, Stavi
Abstract: In the quest to maintain multicultural formal learning environments in a world of diversity, educators must consider the possibility of informal institutions, such as museums, as prototypes for schools with a wide international student base. The collaboration between schools and museums has long been established as best pedagogical practice. This paper looks to investigate this relationship further. It examines how educators in international schools can make use of museum learning theories and practices within their own classrooms. It seeks to answer the question: Can the museum platform, as a representative of cultural multiplicity, offer new approaches to learning that teachers can use to enhance curriculum and exhibit their best practice objectives? Yet, in order to consider this question, we must identify learning which occurs in museums through 'meaning making' in the visitor experience. Museums offer themselves as platforms for the infinite layers of human actions and interactions. They have at their disposal a multitude of innovative resources and strategies, which engage diverse audiences such as objects, interpretive practice and the implementation of constructivist epistemologies. Therefore, schools with an international student base must seek out to museums as sources of educational inspiration and innovation, and in turn explore fresh paths to learning and curriculum enhancement, which are user friendly and culturally dynamic in scope. With these sentiments in mind the project, iteach2! was born, aiming to uncover the unifying potential of museum pedagogy with the diverse realities of formal multicultural learning environments.